(untitled) (Cambridge, UK, 2000)
The book provides an authoritative guide to they key issues in dealing with food intolerance within the food industry. Text explains key terminology and the mechanisms of food intolerance, key issues for those trying to minimize the amount of allergens in food, current labeling requirements and international sources of information on allergens
Keywords: Food allergy,Food,Nutritionally induced diseases; Toxicology